Theological foundations for environmental ethics : reconstructing patristic and medieval concepts - Schaefer, Jame (Georgetown University Press, 2009)
Can religion make a positive contribution to preventing further destruction of biological diversity and ecosystems and threats to our earth? Jame Schaefer thinks that it can, and she examines the thought of Christian Church fathers and medieval theologians to reveal and retrieve insights that may speak to our current plight. By reconstructing the teachings of Augustine, Thomas Aquinas, and other classic thinkers to reflect our current scientific understanding of the world, Schaefer shows how to "green" the Catholic faith: to value the goodness of creation, to appreciate the beauty of.